STUDENTS’ TOPIC INTEREST IN LEARNING ENGLISH BASED ON KURIKULUM MERDEKA AT SMPN IN SUNGAI SERUT DISTRICT IN THE CITY OF BENGKULU - Yustiana, Oka; Mukhrizal; Hardiah, Mei (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2024)
The objectives of this survey research were to find out students’ topic interest in learning English based on Kurikulum Merdeka at SMPN in Sungai Serut District in the City of Bengkulu. The population was 343 grade eighth students and the samples were 134 students. The instrument of the research was questionnaire. In terms of classification, it comprised three aspects (enjoyment, attention, and curiosity). The results of this research showed that some of the students’ topic interest were respectively as followed: Lyrics of the songs (very high interest), paying attention (high interest), ability and willingness in implementing actions (high interest) recount text (high interest), greeting cards, location of things, comparison, and  notice (high interest), obligation and prohibition, and general truth (high interest) command, invitation, and asking for permission (high interest), past activities (high interest) current activities (high interest). Thus, the highest level of students’ interest was lyrics of the songs and the lowest interest was current activities. It was suggested that the teachers should enhance or optimize students' interest in learning English